2014
DOI: 10.1111/nph.12988
|View full text |Cite
|
Sign up to set email alerts
|

Independent allopolyploidization events preceded speciation in the temperate and tropical woody bamboos

Abstract: SummaryThe objectives of the current study were to investigate the origin of polyploidy in the woody bamboos and examine putative hybrid relationships in one major lineage (the temperate woody bamboos, tribe Arundinarieae).Phylogenetic analyses were based on sequence data from three nuclear loci and 38 species in 27 genera.We identify six ancestral genome donors for contemporary bamboo lineages: temperate woody bamboos (tribe Arundinarieae) contain genomes A and B, tropical woody bamboos (tribe Bambuseae) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
101
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 53 publications
11
101
0
1
Order By: Relevance
“…Molecular data have confirmed that the Bambusoideae, especially the two woody tribes, exhibit a complex history of hybridization and allopolyploidy (Fisher et al, 2009Triplett et al, , 2014Goh et al, 2013;Yang et al, 2013;Attigala et al, 2014;Oliveira et al, 2014). Within Arundinarieae, the three traditionally recognized subtribes are polyphyletic and have been abandoned in favor of numbered lineages or clades (now twelve) based on molecular support (cited in Kellogg, 2015 but not in Soreng et al, 2015b), and a number of genera, including Ampelocalamus, Indocalamus, Pleioblastus and Pseudosasa among others, are demonstrably nonmonophyletic Zeng et al, 2010;Yang et al, 2013;Zhang et al, 2016).…”
Section: Bambusoideaementioning
confidence: 96%
“…Molecular data have confirmed that the Bambusoideae, especially the two woody tribes, exhibit a complex history of hybridization and allopolyploidy (Fisher et al, 2009Triplett et al, , 2014Goh et al, 2013;Yang et al, 2013;Attigala et al, 2014;Oliveira et al, 2014). Within Arundinarieae, the three traditionally recognized subtribes are polyphyletic and have been abandoned in favor of numbered lineages or clades (now twelve) based on molecular support (cited in Kellogg, 2015 but not in Soreng et al, 2015b), and a number of genera, including Ampelocalamus, Indocalamus, Pleioblastus and Pseudosasa among others, are demonstrably nonmonophyletic Zeng et al, 2010;Yang et al, 2013;Zhang et al, 2016).…”
Section: Bambusoideaementioning
confidence: 96%
“…Such characters include rhizome structure, presence or absence of pseudospikelets, numbers and arrangement of culm buds and branches, and inflorescence architecture. In addition, homoploid hybridization has been documented and appears to be far more common than previously thought possible (Takahashi et al 1994;Triplett et al , 2014. Several common "genera" appear to be simply early-generation (possibly F1) hybrids that combine the characters of their parent genera.…”
mentioning
confidence: 93%
“…Thus, even very well sampled molecular phylogenies such as those of and Zeng et al (2010) often provide only weak hints of phylogenetic history. Finally, all woody bamboos appear to be polyploid (e.g., Stebbins 1971Stebbins , 1985Triplett et al 2014). Not surprisingly, the first genome sequence of a woody bamboo shows a whole genome duplication event, estimated to have occurred 7-12 mya (Peng et al 2013), although it is unclear if the methods used account for the very slow mutation rate.…”
mentioning
confidence: 96%
See 2 more Smart Citations